Differences in Soil Nutrient Levels in Oil Palm Plantations (Elaeis guineensis Jacq.) Planting Age 6 and 8 Years : - - Oksana; Riska Dian Oktari; Arya Wirandanu (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Oil palm plantations in Riau Province were commonly found on suboptimal lands, such as Inceptisol soils, which exhibited inherently poor soil chemical fertility. This research aimed to determine the chemical properties of Inceptisol soil in 6- and 8-year-old oil palm plantations. This research was conducted from July to December 2024 at the Oil Palm Plantation, Sub-District Perhentian Raja, Kampar District, Riau. The analysis of soil chemical properties was carried out at the Instrumental Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Padang State University. This research employed a quantitative descriptive method, where data collection was conducted through direct observation and subsequently analyzed in the laboratory. A purposive sampling technique was employed to collect soil samples, where each block was divided into four sampling plots. Within each plot, soil samples were collected and composited from five sub-samples, yielding a total of eight Inceptisol soil samples for subsequent analysis. The following soil parameters were analyzed: pH (H2O), OC, total N, P, K, Ca, Mg, SO4, and CEC. The chemical properties of the Inceptisol at the research sites were characterized by: a pH range of very acidic to acidic, sufficient levels of OC, and total-N, very low levels of total (P and K), excessive of total-Ca, deficient of total-Mg, very low levels of SO4, and moderate to high levels of CEC; there were significant mean differences in soil N, SO4, and CEC, whereas soil pH, OC, P, K, Ca, and Mg levels were not influenced by oil palm age.